Diagnostic therapeutic assistance pathway (PDTA) of type 2 chronic rhinosinusitis - Canevari, Frank Rikki; Giorli, Alessia; Monti, Giulia; Biagini, Cesare; Bagnasco, Diego; Cavaliere, Carlo; Pipolo, Carlotta; De Corso, Eugenio; Gelardi, Matteo; Gramellini, Giulia; Ioppi, Alessandro; La Mantia, Ignazio; et al. (Frontiers in Allergy, 2023)
Chronic rhinosinusitis (CRS) is a complex and heterogeneous disorder whose etiopathogenetic picture is not yet completely known and is classically divided into CRS with (CRSwNP) and without nasal polyps (CRSsNP). But today the distinction is made with type 2 and nontype 2 variants. A rational and defined pathway for the diagnosis of chronic rhinosinusitis is an indispensable means to be able to arrive at a correct identification of the patient. This typing is essential to be able to arrive at the correct course of treatment, which turns out to be different for different types of patients. For this reason, the realization of a diagnostic therapeutic pathway represents a fundamental way for the otolaryngologist specialist but not only, since today diagnostics has a multidisciplinary framework. In the present work, precise indications have been developed to arrive at a correct diagnosis. The various diagnostic pathways and processes to arrive at a correct therapeutic framing have been highlighted. Therapy ranging from medical therapy to surgical therapy without neglecting the new biological therapies. It does not represent a guideline but a diagnostic method that can be adapted to all the various territorial realities.